Laudato Si’ and Beyond: An Interfaith Exploration of Integral Ecology and its Implications for Peace, Justice, and Strong Institutions (SDG 16) - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
This qualitative research explores the concept of integral ecology, as outlined in Pope Francis’ Laudato Si’, and its implications for peace, justice, and strong institutions (SDG 16). The study examines two case studies, the Green Belt Movement in Kenya and the Jesuit-run Social Justice and Ecology Secretariat in Rome, to demonstrate the practical applications of integral ecology in promoting sustainable development and social justice. The research integrates insights from various scholarly voices and explores the diversity of interpretations within different Christian denominations. The study finds that Integral ecology provides a holistic approach to understanding the relationships between human dignity, environmental sustainability, and social justice. The case studies highlight the importance of community-led initiatives, environmental justice, and advocacy and community engagement in promoting sustainable development and social justice. The research contributes to the growing body of research on integral ecology and its implications for sustainable development and social justice, providing valuable insights for policymakers, practitioners, and scholars seeking to promote peace, justice, and strong institutions (SDG 16).